Effects of dietary probiotic (Clostridium butyricum I9, C. butyricum G15, or Paraclostridium bifermentans X13) on growth, digestive enzyme activities, immunity, and intestinal microbiota of Pacific white shrimp (Penaeus vannamei) - Yang, Wei; Liang, Huifen; Chen, Ruhan; Du, Zhinuo; Deng, Taoqiu; Zheng, Yuqing; Song, Ying; Duan, Yanchuang; Lin, Junyuan; Bakky, Md. Akibul Hasan; Tran, Ngoc Tuan; Zhang, Ming; et al. (Frontiers in Microbiology, 2024)
Pacific white shrimp (Penaeus vannamei) is one of the most productive and economically important species globally. However, the development and continuous expansion of the farming scale led to an increase in the risk of disease occurrence in shrimp farming. The application of probiotics as an effective method for controlling diseases in aquaculture has been widely considered. In shrimp farming, several probiotics have been used and shown benefits to the health of the host. To diverse the sources of bacterial species as probiotics in shrimp farming, in this study, we aimed to elucidate the effects of dietary probiotics (Clostridium butyricum I9 (I9), Clostridium butyricum G15 (G15), or Paraclostridium bifermentans X13) on the growth, immune response and intestinal microbiome of white shrimp. Shrimps were fed with diets containing either phosphate-buffered saline (PBS), I9 (107 CFU/g feed), G15 (107 CFU/g feed), or X13 (107 CFU/g feed) for 30 days and followed by the challenge with Vibrio parahaemolyticus (Vp). The results showed that the survival rate, body weight gain, and special growth rate of shrimps in the I9, X13, and G15 groups significantly increased, compared to the PBS. The supplementation of probiotics increased the content of short-chain fatty acids and effectively maintained the normal morphology and structure of the intestinal tract and hepatopancreas. The I9, X13, or G15 groups showed a positive change in the diversity and abundance of gut bacteria. There was a significant up-regulation of CTL, SOD, proPO, Crustin, PEN2-4, and ALF1-3 genes in shrimps in the I9, X13, and G15. Additionally, dietary probiotics significantly increased the survival rate, maintained the intestinal structure, promoted the activities of SOD, AKP, ACP, and T-AOC enzymes, and reduced the level of MDA in shrimps after Vp infection. In conclusion, dietary supplementation of I9, G15, or X13 improved the growth, immunity, and disease resistance of Pacific white shrimp, providing a scientific basis for shrimp farming.